Facilitators and Barriers to Electronic Personal Health Record Use in the Older Adult Population - (:unkn) unknown (My University, 2022)
Technology is rapidly being implemented into healthcare. The electronic personal health record (ePHR) has been implemented to improve health outcomes, patient engagement, self-management of chronic disease, and decrease cost of healthcare. Research has examined the impact on older adult’s ePHR use, and which characteristics influence an older adult’s willingness to use the ePHR. However, there is little evidence to describe facilitators and barriers, and the hypothesized consequences. A correlational design with a convenience sample of older adults (n = 210). Measures included a self-reported survey, adapted U.S.A.B.I.L.I.T.Y. survey, Geriatric Depression Scale: Short Form, UCLA Loneliness Scale, and an observation checklist. Descriptive statistics, frequency distributions, Pearson r and standard multiple regression used for data analysis. Multiple regression analysis for the dependent variable of intent to use indicates the overall model explains 70.3% of the total variance in older adults’ intent to use ePHR (F (7, 200) = 67.6, p